2007
DOI: 10.1007/s11274-007-9369-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of culturing conditions of Porphyridium cruentum using uniform design

Abstract: The red microalga Porphyridium contains many valuable compounds such as polysaccharides, polyunsaturated fatty acids, and phycoerythrin (PE). In this study, a uniform design method and regression analysis were used to investigate the effects of initial pH, light intensity, inoculation ratio, and liquid volume in flask on the optimal biomass, exopolysaccharides (EPS), and PE production of Porphyridium cruentum in a batch culture at laboratory scale. Using regression analysis, we obtained the models to clarify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 23 publications
0
13
2
1
Order By: Relevance
“…Under this renewal condition, the maximum total recovery yields of biomass and polysaccharide were 197.08g and 26.81g, respectively. The mean production arrived at 9.854 g/L and 1.34 g/L, which were higher than the previous report [15,16], and also were 3.7 times and 1.38 times higher than that in batch culture.…”
Section: Discussioncontrasting
confidence: 74%
“…Under this renewal condition, the maximum total recovery yields of biomass and polysaccharide were 197.08g and 26.81g, respectively. The mean production arrived at 9.854 g/L and 1.34 g/L, which were higher than the previous report [15,16], and also were 3.7 times and 1.38 times higher than that in batch culture.…”
Section: Discussioncontrasting
confidence: 74%
“…This part of the investigation was aimed to verify if the laboratory results reflected the field observations by studying the effect of the three components on the strength and spectrum of activity of seven Streptomyces strains through laboratory shake flask cultivation following the one-factor-at-a-time approach (Wang et al 2007) utilizing standard microbiological medium ingredients. Seven of the eleven Streptomyces strains showing broad-spectrum activity against the highest number of test bacteria as well as high values of the zone of inhibition were used in this study so that the experimental data could be clearly differentiated.…”
Section: Gram-negative Bacteriamentioning
confidence: 99%
“…The results confirmed that semi-continuous culture mode was more efficient for increasing the production. In this study, the maximal output rate of polysaccharide was 68.64 mg/L per day, which was 2.02 times higher than the one cultivated in 20 cm LP flat plate photobioreactor 15 L. The polysaccharide concentration of P. cruentum cultured in batch or semicontinuous mode were mostly in the ranged of 500-950 mg/L [1,6,14]. Although some researchers reported higher polysaccharide concentration [10,24], they cultured the alga in 80 mL glass tubes.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies have shown that nutrient and light availability affected the production of cell biomass and extracellular polysaccharides [6][7][8]. Nitrogen determines the production of polysaccharides and influences the secretion of soluble polysaccharides [9].…”
Section: Introductionmentioning
confidence: 99%